Explaining interindividual differences in toddlers' collaboration with unfamiliar peers: individual, dyadic, and social factors - Schuhmacher, Nils; Kärtner, Joscha (Frontiers in Psychology, 2015)
During their third year of life, toddlers become increasingly skillful at coordinating their actions with peer partners and they form joint commitments in collaborative situations. However, little effort has been made to explain interindividual differences in collaboration among toddlers. Therefore, we examined the relative influence of distinct individual, dyadic, and social factors on toddlers’ collaborative activities (i.e., level of coordination and preference for joint activity) in joint problem-solving situations with unfamiliar peer partners (n = 23 dyads aged M = 35.7 months). We analyzed the dyadic nonindependent data with mixed models. Results indicated that mothers’ expectations regarding their children’s social behaviors significantly predicted toddlers’ level of coordination. Furthermore, the models revealed that toddlers’ positive mutual experiences with the unfamiliar partner assessed during an initial free play period (Phase 1) and their level of coordination in an obligatory collaboration task (Phase 2) promoted toddlers’ preference for joint activity in a subsequent optional collaboration task (Phase 3). In contrast, children’s mastery motivation and shyness conflicted with their collaborative efforts. We discuss the role of parents’ socialization goals in toddlers’ development toward becoming active collaborators and discuss possible mechanisms underlying the differences in toddlers’ commitment to joint activities, namely social preferences and the trust in reliable cooperation partners.